Basic medical advice for travelers to high altitudes - Schommer, Kai; Bärtsch, Peter (Deutsches Ärzteblatt, 2011)
Trekking and culture-oriented vacations in Tibet and the Andes have become highly popular. Persons who have never journeyed to high altitudes before are now booking trips to mountains that can be climbed relatively easily despite altitudes of 5000 to...